Dynamic loading response of an additively produced bio-inspired nacre structure with foam and acrylic filling - Adithya, RN; Balan Ganapathy, Sakthi; Sakthivel, Aravind Raj; Hameed Sultan, Mohamed Thariq; Shahar, Farah Syazwani (SAGE Publications, 2024)
Numerous structures gain inspiration from nature and have been effectively incorporated into different applications such as automobiles and airplanes. In order to effectively withstand impact loads and achieve efficient energy absorption, it is necessary to incorporate appropriate structures along with suitable filler materials. This study examines the energy absorption capacities of a nacre structured core with foam filling at the central nacre cell cavities, as well as an acrylic filling at the top and bottom sides, under low velocity impacts. The design of experiments involved identifying and varying three important design parameters which influence the energy absorption behavior of the composites. Subsequently, fillers were incorporated and the specimens were subjected to drop weight testing. The composite material exhibited minimal deformations while absorbing a maximum energy of 40.87 J. Therefore, it proved that this composite could withstand dynamic impact loads in the absence of fiber face sheets, and adhesion between the PLA-carbon fiber and acrylic fill was also improved under these conditions. The higher energy absorption behavior was obtained due to the intermittent force transfer in the transverse direction due to the presence of the cross webs on the top and bottom of the composite plate. The alternate arrangement of the hard and flexible materials in the composite leads to the suppression of the stress step by step which results in high energy absorption behavior. In order to achieve optimal energy absorption with minimized deformations, the core structure must possess a nacre wall thickness of 2 mm with double cross web design.